2023
DOI: 10.1039/d2nr05678j
|View full text |Cite
|
Sign up to set email alerts
|

Hafnium-doped zirconia ferroelectric thin films with excellent endurance at high polarization

Abstract: Using thermal atomic layer deposition and subsequent rapid thermal annealing without the need of metal clamping atop, a remanent polarization (Pr) of 25.5 μC/cm2 was achieved in 10 nm-thick ZrO2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
3
5
0
Order By: Relevance
“…Unfortunately, although significant efforts have been made to understand the mechanism of electrode materials in promoting the ferroelectric performance of PMA-treated HfO 2 -based thin films, the investigation of electrodes for PDAtreated fluorite-structure ferroelectrics are still far from systematic. Moreover, similar to hafnia, the ferroelectricity in pure zirconia thin films has also recently been experimentally confirmed in our lab as well as others [27,28]. Moreover, we reported that Hf-doping can enhance the ferroelectricity in zirconia-based thin films, and the PDA-processed Zr 0.75 Hf 0.25 O 2 (ZHO) exhibits larger ferroelectric polarization and better endurance than PMA-processed ZHO [28].…”
Section: Introductionsupporting
confidence: 78%
See 1 more Smart Citation
“…Unfortunately, although significant efforts have been made to understand the mechanism of electrode materials in promoting the ferroelectric performance of PMA-treated HfO 2 -based thin films, the investigation of electrodes for PDAtreated fluorite-structure ferroelectrics are still far from systematic. Moreover, similar to hafnia, the ferroelectricity in pure zirconia thin films has also recently been experimentally confirmed in our lab as well as others [27,28]. Moreover, we reported that Hf-doping can enhance the ferroelectricity in zirconia-based thin films, and the PDA-processed Zr 0.75 Hf 0.25 O 2 (ZHO) exhibits larger ferroelectric polarization and better endurance than PMA-processed ZHO [28].…”
Section: Introductionsupporting
confidence: 78%
“…Moreover, similar to hafnia, the ferroelectricity in pure zirconia thin films has also recently been experimentally confirmed in our lab as well as others [27,28]. Moreover, we reported that Hf-doping can enhance the ferroelectricity in zirconia-based thin films, and the PDA-processed Zr 0.75 Hf 0.25 O 2 (ZHO) exhibits larger ferroelectric polarization and better endurance than PMA-processed ZHO [28].…”
Section: Introductionsupporting
confidence: 78%
“…In addition, orthorhombic phase has been also stabilized in ZrO 2 films enabling polarization values up to 50 μC cm −2 . [44,45] Thus additional positive contribution of this largely polarizable phase can further promote the good performance of ZrO 2 capped samples. Alternatively, the opposite band bending expected due to the different electron affinity of HfO 2 and ZrO 2 , [46] can also result in a similar effect, i.e., accumulation of oxygen defects in one case and not in the other.…”
Section: Discussionmentioning
confidence: 99%
“…The ferroelectricity of the ZrO 2 thin film was experimentally revealed in a Pt/ZrO 2 (6.1–19.6 nm)/Pt structure . Further investigations revealed that the ferroelectricity of ZrO 2 films can be influenced by many factors, such as doping, film thickness, , epitaxial strain, interfacial layers, electrode material, and oxygen source dose time . It was found that the macroscopic ferroelectric responses can be ascribed to the formation of the orthorhombic or rhombohedral (r) phase in the ZrO 2 films. , …”
Section: Introductionmentioning
confidence: 99%
“…To obtain a ferroelectric ZrO 2 film, one method is to introduce an in-plane tensile strain to stabilize the ferroelectric o phase . It has been reported that the in-plane tensile strain after rapid thermal processing (RTP) can be introduced by utilizing an electrode material with a lower thermal expansion coefficient (TEC) than that of the ferroelectric layer (the TEC of ZrO 2 is ∼10.5 × 10 –6 K –1 ). , For example, by utilizing a low-TEC tungsten electrode (∼4.5 × 10 –6 K –1 ), a remnant polarization ( P r ) of ∼21.5 μC/cm 2 can be achieved in the W/ZrO 2 (10 nm)/W structure, but the leakage current density is high (∼5 × 10 –7 A/cm 2 at 1 MV/cm) as a result of the oxygen vacancy (V O ) generated during the interfacial oxidation of W. , In comparison to ZrO 2 , RuO 2 also has a low TEC of ∼6.4 × 10 –6 K –1 and may contribute to stabilizing the ferroelectric o phase in ZrO 2 . Moreover, the interfacial oxygen diffusion from RuO 2 to ZrO 2 can suppress the V O concentration in the ZrO 2 film and reduce the leakage current. Therefore, investigating the ferroelectricity of ZrO 2 with RuO 2 electrodes and ferroelectric-ZrO 2 -based ferroelectric field-effect transistors (FeFETs) can be innovative.…”
Section: Introductionmentioning
confidence: 99%